2006
DOI: 10.1007/s00256-006-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of MRI in classifying proximal focal femoral deficiency

Abstract: MRI is more accurate than radiographic evaluation for the classification of PFFD, particularly early on, prior to the ossification of cartilaginous components in the femurs. Since radiographic evaluation tends to overestimate the degree of deficiency, MRI is a more definitive modality for evaluation of PFFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…It ranges from mild shortening to severe deficiency of the femoral head, acetabulum, and femoral shaft. PFFD diagnosis requires a shortened femur with proximal femoral deficiency and therefore deficiency of the iliofemoral articulation, leg length discrepancy, limb malrotation, and varus deformity at the subtrochanteric level (24). Fifteen percent of cases have bilateral involvement (11).…”
Section: Proximal Focal Femoral Deficiencymentioning
confidence: 99%
“…It ranges from mild shortening to severe deficiency of the femoral head, acetabulum, and femoral shaft. PFFD diagnosis requires a shortened femur with proximal femoral deficiency and therefore deficiency of the iliofemoral articulation, leg length discrepancy, limb malrotation, and varus deformity at the subtrochanteric level (24). Fifteen percent of cases have bilateral involvement (11).…”
Section: Proximal Focal Femoral Deficiencymentioning
confidence: 99%
“…The growth ratio of the abnormal to the normal limb throughout childhood is usually constant [4]. The Amstutz classification [5], another common classification system, has also been used in PFFD and has been applied to MRI [6].…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that these features of Case 2 represented Aitken class A deformity, the mildest form of PFFD. Maldjian et al [6] used MRI in diagnosis and classification of PFFD, stating that MRI was more accurate than radiographic evaluation for the classification of PFFD, particularly prior to the ossification of cartilaginous components in the femurs. MRI has perfect contrast resolution and it is superior to US in demonstrating all the bony elements (femoral head, femoral neck and shaft, acetabulum, iliac bone) and cartilage together, in clearly depicting their relationship with each other, and in showing any impingement [8], regardless of any limiting factor experienced with US, such as adverse effects of tissue thickness and acoustic shadowing caused by bone.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10 MRI should be considered the modality of choice when assessing PFFD because of its ability to demonstrate the anatomy of the cartilaginous and bony proximal femur, which can facilitate appropriate treatment. 3,4,11 Osteo-articular infections in neonates are rare and usually present in an atypical way compared to older children. 12 Wilson et al 12 showed that infants can often have a worse outcome compared to older patients in their series possibly due to a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%